2017
DOI: 10.1111/joor.12487
|View full text |Cite
|
Sign up to set email alerts
|

Accounts of bullying on Twitter in relation to dentofacial features and orthodontic treatment

Abstract: Social media offers an accessible resource for gaining valuable insights into the social culture of bullying. The purpose of this study was to qualitatively analyse Twitter posts for common themes relating to dentofacial features, braces and bullying. Twitter's database was searched from 2010 to 2014 using keywords relevant to bullying, teeth and orthodontics. Two investigators assessed the Twitter posts, and selected those that conveyed the experiences or opinions of bullying victims. The posts were qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 34 publications
0
46
0
Order By: Relevance
“…They identified cases of bullying, qualified them, and looked for coping mechanisms the victims and their families had for the mistreatment. 76 These studies demonstrate the value of data gleaned from social media. Data gathered from social media demonstrates that researchers can measure the positive or negative impact of psychosocial variables on oral health.…”
Section: Where To Gather Datamentioning
confidence: 79%
See 1 more Smart Citation
“…They identified cases of bullying, qualified them, and looked for coping mechanisms the victims and their families had for the mistreatment. 76 These studies demonstrate the value of data gleaned from social media. Data gathered from social media demonstrates that researchers can measure the positive or negative impact of psychosocial variables on oral health.…”
Section: Where To Gather Datamentioning
confidence: 79%
“…Another study looked at bullying on Twitter related to dentofacial features and orthodontic treatment. They identified cases of bullying, qualified them, and looked for coping mechanisms the victims and their families had for the mistreatment . These studies demonstrate the value of data gleaned from social media.…”
Section: Discussionmentioning
confidence: 98%
“…Parents were approached through social networking sites as these are very popular in Saudi Arabia. Chen et al [23] also reported that the public was more comfortable sharing personal bullying experiences on publicly accessible social media forums such as Twitter.…”
Section: Study Population and Ethical Approvalmentioning
confidence: 99%
“…16 Although few studies have specifically evaluated the efficacy of social media on orthodontic treatment and marketing knowledge, hasn't been studied with the use of Google Trends data on changes internet searches globally over years. [17][18][19] The aim of study is to examine the interest in orthodontics in the last 5 years using Google Trends data all over the world.…”
Section: Introductionmentioning
confidence: 99%